Financial Literacy and Investment Behavior of Nepalese Investors - Gurung, Rajesh; Oli, Prabha; Dahal, Pramod (Journal of Nepalese Management and Research, 2025)
This research assesses the linkage between financial literacy and investment choice among Nepalese individuals, addressing the growing complexity of financial markets in developing economies. The research explores how financial literacy, measured by financial knowledge, skills, attitude, and behavior, affects investment decisions, with a focus on the mediating role of investment confidence. A descriptive and causal-comparative research design was employed to analyze data from 397 participants, including the general public, investors, and financially literate individuals from diverse backgrounds. The results confirmed that all the facets of financial literacy positively influence investment decisions: financial knowledge (β = 0.091, p < 0.05), financial skills (β = 0.099, p < 0.05), financial attitude (β = 0.192, p < 0.05), and financial behavior (β = 0.807, p < 0.05), with financial behavior showing the strongest effect. While financial knowledge negatively impacted investment confidence (β = -0.067, p < 0.05), financial skills, attitude, and behavior had positive effects, with financial attitude having the most significant influence (β = 0.723, p < 0.05). Investment confidence significantly mediates the relationship between financial literacy and investment choices (β = 0.832, p < 0.05), suggesting that confidence strengthens individuals’ ability to operationalize financial competencies in their decision-making process. The findings suggest important policy level implications, emphasizing the need to prioritize the market transparency and investor protection initiatives to enhance investor self-efficacy and reduce perceived risks. Future research could explore the negative association between financial knowledge and investment decisions, and longitudinal data can further reveal the dynamics of investment behavior over time.